Overexpression of acetyl-CoA carboxylase in Aspergillus terreus to increase lovastatin production - Hasan, Hanan; Abd Rahim, Muhammad Hafiz; Campbell, Leona; Carter, Dee; Abbas, Ali; Montoya, Alejandro (Elsevier, 2018)
The present work describes the application of homologous recombination techniques in a wild-type Aspergillus terreus (ATCC 20542) strain to increase the flow of precursors towards the lovastatin biosynthesis pathway. A new strain was generated to overexpress acetyl-CoA carboxylase (ACCase) by replacing the native ACCase promoter with a strong constitutive PadhA promoter from Aspergillus nidulans. Glycerol and a mixture of lactose and glycerol were used independently as the carbon feedstock to determine the degree of response by the A. terreus strains towards the production of acetyl-CoA, and malonyl-CoA. The new strain increased the levels of malonyl-CoA and acetyl-CoA by 240% and 14%, respectively, compared to the wild-type strain. As a result, lovastatin production was increased by 40% and (+)-geodin was decreased by 31% using the new strain. This study shows for the first time that the metabolism of Aspergillus terreus can be manipulated to attain higher levels of precursors and valuable secondary metabolites.